2023
DOI: 10.3390/nano13071249
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phenol via an Advanced Oxidation Process (AOP) with Immobilized Commercial Titanium Dioxide (TiO2) Photocatalysts

Abstract: Four commercial titanium dioxide (TiO2) photocatalysts, namely P25, P90, PC105, and PC500, were immobilized onto steel plates using a sol-gel binder and investigated for phenol degradation under 365 nm UV-LED irradiation. High-performance liquid chromatography (HPLC) and total organic carbon (TOC) analyses were performed to study the impact of three types of oxygen sources (air, dispersed synthetic air, and hydrogen peroxide) on the photocatalytic performance. The photocatalyst films were stable and there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Due to its abundance, low toxicity, and price, TiO 2 has been used as nanoparticles or nanocomposites for photocatalytic degradation. Schwarze et al [181] reported the immobilization of four commercial TiO 2 onto steel plates for phenol degradation, using H 2 O 2 as an oxygen source. Although all the systems proved to be stable, the commercial TiO 2 P90 (crystallite size 13 nm; surface area 103 m 2 /g; anatase: rutile composition 87: 13; band gap 3.3 eV) outperformed the rest, with a 100% degradation of phenol within 3 h.…”
Section: Nanomaterials For the Photodegradation Of Pollutantsmentioning
confidence: 99%
“…Due to its abundance, low toxicity, and price, TiO 2 has been used as nanoparticles or nanocomposites for photocatalytic degradation. Schwarze et al [181] reported the immobilization of four commercial TiO 2 onto steel plates for phenol degradation, using H 2 O 2 as an oxygen source. Although all the systems proved to be stable, the commercial TiO 2 P90 (crystallite size 13 nm; surface area 103 m 2 /g; anatase: rutile composition 87: 13; band gap 3.3 eV) outperformed the rest, with a 100% degradation of phenol within 3 h.…”
Section: Nanomaterials For the Photodegradation Of Pollutantsmentioning
confidence: 99%